The Relationship Between Maternal Knowledge and Stunting Prevention Practices Among Children at Alisah Clinic in 2026 - Ermita Silvana Putri; Eni Monaliska Sihombing (International Journal of Public Health Excellence (IJPHE), 2026)
Stunting is a health issue that is currently a major concern, particularly in Indonesia. Stunting is a condition in which a child experiences growth impairment, resulting in shorter stature. Low levels of maternal knowledge influence mothers’ behavior in providing balanced nutrition to their children. This study aims to analyze the relationship between maternal knowledge and preventive measures against stunting in children at the Alisah Clinic in 2026. This study is an analytical survey using a cross-sectional approach. The study population consisted of mothers with children under 5 years of age at Alisah Clinic. The sample comprised 40 participants selected using accidental sampling. The results showed that of the 40 respondents with children under 5 years of age, the majority 23 respondents (57.5%) had knowledge categorized as “inadequate,” while a minority 8 respondents (20.0%) had knowledge categorized as “good.” Of the 40 respondents with children under 5 years of age, the majority 29 respondents (72.5%) did not take preventive measures, while a minority 11 respondents (27.5%) did. Of the 40 respondents regarding stunting prevention who have children under 5 years of age, the majority 22 respondents (55.0%) did not take any preventive measures, while a minority 18 respondents (45.0%) did. There is a relationship between mothers’ actions and the prevention of stunting in children. At a 95% confidence level with α = 0.005%, the two-tailed significance value (sig) was 0.00 < 0.05. The conclusion of this study is that there is a relationship between mothers’ knowledge and preventive measures against stunting in children at the Alisah Clinic in 2026. It is recommended that mothers further improve their knowledge regarding the prevention of stunting in children through educational sessions or other sources of information.